2016
DOI: 10.1188/16.onf.306-315
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic Health Among Cancer Survivors: A 13-Week Pilot Study of a Combined Aerobic and Resistance Training Program

Abstract: CART may be a plausible alternative to reduce the risk of metabolic syndrome and improve cardiometabolic health among cancer survivors. Additional studies that continue to explore the efficacy and effectiveness of CART may provide more information to help nurses and physicians determine whether the cancer survivorship care plan should include an exercise-based alternative to intervene on cardiometabolic health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Survivor studies with information on altered biomarker values but no direct comparison between biomarker and MetS occurrence were excluded. 60 , 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 We expected to miss many relevant studies when designing the study, if we based our conclusions only on survivor studies. Therefore, evidence in the younger general adult population without childhood cancer history was included in our search as well, leading to 175 general population studies with relevant data which were generalizable to young adult survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Survivor studies with information on altered biomarker values but no direct comparison between biomarker and MetS occurrence were excluded. 60 , 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 We expected to miss many relevant studies when designing the study, if we based our conclusions only on survivor studies. Therefore, evidence in the younger general adult population without childhood cancer history was included in our search as well, leading to 175 general population studies with relevant data which were generalizable to young adult survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Bao et al37) evaluated the impact of exercise in a population-based prospective cohort study of 1,696 breast cancer survivors and showed that exercise was inversely associated with the prevalence of metabolic syndrome, and that regular exercise participation reduced its prevalence. Similarly, Grote et al38) studied the effects of exercise on patients who had survived different types of cancer, and their findings showed that a 3 day/week, 13-week exercise intervention improved the cardiometabolic health of cancer survivors. These investigators noted that the intervention was less effective in non-Caucasian survivors compared with Caucasian survivors, which warrants undertaking larger, multiethnic studies.…”
Section: Studies Into Intervention and Preventionmentioning
confidence: 99%
“…The nature of training programs used with cancer survivors has remained a focus of research in an effort to devise the most effective strategy for fulfilling the needs of survivors. For instance, Grote et al investigated the efficacy of combined aerobic and resistance training for cancer survivors [22]. They found that improvement in cardiometabolic health is critical for preventing comorbidity among cancer survivors; in fact, it is as important as monitoring for the possible recurrence of cancer [22].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Grote et al investigated the efficacy of combined aerobic and resistance training for cancer survivors [22]. They found that improvement in cardiometabolic health is critical for preventing comorbidity among cancer survivors; in fact, it is as important as monitoring for the possible recurrence of cancer [22]. Further, Ligibel indicated the need to control for “energy balance factors, including diet, PA, and body weight,” in order to reduce the risk of cancer recurrence following treatment [23].…”
Section: Resultsmentioning
confidence: 99%